Cross‐Linked Polymers as Scaffolds for the Low‐Temperature Preparation of Nanostructured Metal Oxides. Issue 42 (9th July 2020) - Centomo, Paolo; Zecca, Marco; Biffis, Andrea
Abstract: The current state of the art of the use of cross‐linked organic polymers, both insoluble (resins or gels) and soluble (micro‐ and nanogels), as aids for the low‐temperature preparation of stable metal oxide nanoparticles or nanostructured metal oxides is reviewed herein. Synthetic strategies for inorganic oxide nanomaterials of this kind can greatly benefit from the use of cross‐linked polymers, which may act as scaffolds/exotemplates during inorganic nanoparticle synthesis, or as stabilizers following post‐synthetic modification of the nanoparticles. Furthermore, the peculiar properties of the organic cross‐linked polymers add to those of the inorganic oxide nanoparticles, producing materials with combined properties. The potential applications of such highly promising composite nanomaterials will be also briefly sketched. Abstract : Linking up : An overview is presented on the current state of the art in the use of crosslinked organic polymers in the preparation of hybrid materials containing metal oxide nanoparticles into them. Both insoluble crosslinked polymers (resins) and soluble ones (micro‐ and nanogels) are considered. The review focuses on the synthetic strategies that have been proposed and sketches the current applications of the resulting materials.